PENGARUH MANAJEMEN PENINGKATAN MUTU SEKOLAH, PERBAIKAN MUTU SEKOLAH BERKELANJUTAN, BUDAYA SEKOLAH, PENDIDIKAN SEKOLAH DASAR YANG ISLAMI, TERHADAP KEPUASAN PELANGGAN (ORANG TUA SISWA SDI AL-AZHAR 14 SEMARANG) - Hadikusumo, Kunaryo (Jurnal Penelitian Pendidikan, 2012)
The purpose of this research was to know how much influence school quality increase management, continuous quality improvement school, school culture, and an Islamic elementary school educationto customer satisfaction. The research population was parents of SDI Al-Azhar 14 Semarang, amounting to 726 people. The sampling technique using proportional random sampling of 200 parents. Captured by structured scales of questionnaires and the data analyzed with simple regression used SPSS programe. The results showed that increase the school quality of management, continuous improvement of school quality, school culture, and an Islamic elementary school education influence customer satisfaction, either partially or together. The findings are as follows: the school quality of management (X ) influenced customer satisfaction (Y) of 68.5%, continuous improvement of school quality (X 1 ) affects customer satisfaction (Y) of 72.0%, school culture (X 3 2 ) influencedcustomer satisfaction (Y) for 70.2%, and an Islamic elementary school education (X ) influenced customer satisfaction (Y) of 72.3%. Meanwhile, the the school quality of management (X 4 ), continuous improvement of school quality (X 2 ), school culture (X ), and an Islamic elementary school education (X 4 3 ) influenced elementary (Y) jointly for 83.3%. The implications for school admissions policy in the preparation of learners and improving the quality of schools and improve services to stakeholders, the school committee (jam`iyyah), so that parents feel satisfied, pleasure, and conveniently send their sons and daughters of SDI Al-Azhar 14 Semarang. 1